(untitled) (African Journal of Biomedical Research, 2022)
This study was designed to assess the effect of board game-based nutrition education on breakfast knowledge, attitude and habit of in-school adolescents in Ile-Ife, Nigeria. The quasi-experimental study involved 360 in-school adolescents assigned into Participatory Experimental (PEG), Experimental (EG) and Control groups (CG) of 120 each. An interviewer-administered questionnaire was used to collect information on respondents’ basic characteristics as well as knowledge, attitude and practices on breakfast consumption. A ‘Breakfast Master’ board game, developed with PEG was used for a 3-week intervention period among the experimental groups. Knowledge was assessed using 11-point scale, categorized as good (≥9) or poor (<9). Attitude was assessed using 50-point scale, categorized as positive (≥34) or negative (<34). Data were analyzed using descriptive statistics and ANOVA at p=0.05. Age of adolescents (CG:13.3±2.2years, PEG:13.9±2.4years, EG: 13.0±2.4years) was similar. Females constituted 55% in CG, 50.9% in PEG and 54.2% in EG, respectively. Change in adolescents with good knowledge (60.8-61.7%, 80.0-94.2%, and 85.8-92.5%) and attitudes (-10.9%, 11.7% and 5.8%) was significant in CG, PEG and EG, respectively. Regular breakfast intake increased from 45.0-42.5%, 70.0-74.1%, and 56.7-70.0%, in CG, PEG, and EG, respectively. Consumption of staple foods during breakfast and proper timing of breakfast meals increased in interventions groups;. Board-game based nutrition education enhanced breakfast habit among in-school adolescents and the use of participatory approach in development of intervention tool heightened knowledge, attitude and practice change.